THE OPTIMAL ANTISEPTIC’S SELECTION FOR PROCESSING BONE CAVITY DURING A SURGICAL TREATMENT OF RADICULAR CYSTS FESTER - V.Y. Potapov; E.N. Vakulenko; Y.D. Protasenko (Український стоматологічний альманах)
Radicular cysts of the jaws and occur arise in the development of chronic inflammation around the tooth root often. Education radicular cyst is often accompanied by the inflammatory processes.